Stellar graveyards: clustering of compact objects in globular clusters NGC 3201 and NGC 6397. Issue 1 (10th June 2022) - Vitral, Eduardo; Kremer, Kyle; Libralato, Mattia; Mamon, Gary A; Bellini, Andrea
ABSTRACT: We analyse Gaia EDR3 and re-calibrated HST proper motion data from the core-collapsed and non-core-collapsed globular clusters NGC 6397 and NGC 3201, respectively, with the Bayesian mass-orbit modelling code MAMPOSSt-PM . We use Bayesian evidence and realistic mock data sets constructed with Agama to select between different mass models. In both clusters, the velocities are consistent with isotropy within the extent of our data. We robustly detect a dark central mass (DCM) of roughly $1000\, \rm M_\odot$ in both clusters. Our MAMPOSSt-PM fits strongly prefer an extended DCM in NGC 6397, while only presenting a mild preference for it in NGC 3201, with respective sizes of a roughly one and a few per cent of the cluster effective radius. We explore the astrophysics behind our results with the CMC Monte Carlo N -body code, whose snapshots best matching the phase space observations lead to similar values for the mass and size of the DCM. The internal kinematics are thus consistent with a population of hundreds of massive white dwarfs in NGC 6397, and roughly 100 segregated stellar-mass black holes in NGC 3201, as previously found with CMC . Such analyses confirm the accuracy of both mass-orbit modelling and Monte Carlo N -body techniques, which together provide more robust predictions on the DCM of globular clusters (core-collapsed or not). This opens possibilities to understand a vast range of interesting astrophysical phenomena in clusters, such as fast radio bursts, compact object mergers, and gravitational waves.